Vivero Internacional de Mustia Hilachosa del Frijol (VIM): Resultados 1973-1985 - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
The purpose of the Bean Web Blight International Nursery (VIM) is to evaluate the degree of resistance or tolerance to Thanatephorus cucumeris of bean var. or advanced lines, and select genes to be incorporated to commercial var. in the different countries where the disease is a constraint to production. Results are summarized of the research on bean web blight conducted in Costa Rica, Nicaragua, Guatemala, Panama, Belize, Colombia, Mexico, Dominican Republic, and Peru, during 1973-85. A list of the bean lines resistant to T. Cucumeris, selected from the VIM, is included. (CIAT)